Boneka Berbicara Sebagai Media Pembelajaran Anggota Tubuh Manusia Untuk Anak Usia Dini - Dwi Cahyono; Wahyu Saputra; Anik Vega Vitianingsih (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
Certain types of learning can be provided through the use of media, including the use of print media, displays, audio, video, visuals, multimedia, and other media intended to facilitate learning. Learning should also begin at an early age, starting with simple basics such as introducing the human body and introducing the limbs of the human body. One of them can use the media in the form of a doll that can give orders to children. Understanding the human body, this study focuses on the introduction of the human body. Especially in early childhood, by using doll-shaped media that can be commanded to touch the doll's limbs. The methodology used in this study is research and development in which this study analyzes needs, manufactures products, and tests the effectiveness of manufactured products. The results of this study are shown using the results of accuracy, memory, and accuracy tests. The final result of the accuracy test is 71%, memory is 90%, and accuracy is 66%. In other words, Talking Doll can be used as an overall alternative. A medium for learning human limbs in early childhood., Although the accuracy of the speaking doll needs to be optimized.Keywords— Talking dolls, learning media, childhood, body parts